Partitioning, leachability, and speciation of chromium in the size-fractions of soil contaminated by chromate production. (January 2021) - Zhang, Zhuo; Guo, Guanlin; Zhao, Huafu; Wu, Dan
Abstract: Soil particle size significantly affects the distribution and migration of chromium (Cr) in soil. Limited studies have investigated the impact of soil particle size on Cr partitioning at chromate contaminated sites. In this study, the physicochemical properties of coarse sand, medium sand, fine sand, and silt-clay were analyzed. And the particle size effects on partitioning, leachability, and bioaccessibility of total Cr and Cr(VI) were determined. The results showed the distribution factor (DF) of Cr(VI) in the coarse sand, medium sand, fine sand, and silt-clay fractions were 0.70, 0.79, 1.35, and 1.60, respectively. The total Cr DF values also had the similar result. The leached concentrations of total Cr and Cr(VI) in silt-clay (562.89 mg/L and 551.71 mg/L) was higher than in coarse sand (238.55 mg/L and 228.68 mg/L) fraction. The bioaccessibility of total Cr and Cr(VI) in silt-clay (77.72% and 88.58%) was higher than in fine sand (60.72% and 79.55%) fraction. The total Cr proportion of the exchangeable fraction (45.92%–73.67%) was relatively high in the four soil particle size fractions and gradually increased as soil particle size decreased. These implied that finer soil particles are more capable of enriching, mobilizing, and bioaccessibility of Cr and Cr(VI) than the coarse particles, which was related to the higher organic matter, cation exchange capacity, specific surface area, and clay components in smaller particles. The results suggested that higher environmental risk occurred in the finer fraction than in the coarser fraction for the chromate production contaminated soil. Graphical abstract: Image 1 Highlights: Four size fractions exhibited the obvious differences in physicochemical properties. The finer soil particles are more capable of enriching Cr and Cr(VI). The finer particles had higher leachability and bioaccessibility of Cr and Cr(VI). The total Cr speciation in finer size fractions appeared to be more unstable.